Metabolic Syndrome - Calderon Velasco, Rolando (2015)
The high incidence of metabolic diseases such as diabetes and obesity, which are taking pandemic proportions in the world, requires that all medical specialties pay attention to metabolic disorders that can present their patients, since in many there metabolic disorders need to know to properly treat.